Parent-Child Mindfulness-Based Training: A Feasibility and Acceptability Study - Courtney H. Guenther PhD; Rebecca L. Stephens PhD; Macy L. Ratliff MS; Sarah J. Short PhD (SAGE Publishing, 2021)
Stress in young children can interfere with academic achievement. To help address stress and aid in developing beneficial lifelong coping skills, educational systems are more widely incorporating programs that teach social and emotional regulation, such as mindfulness-based programs. The effects of these programs may be strengthened through parental support in the home environment. This study examined the feasibility and acceptability of a new Parent-Child Mindfulness-Based Training (PC-MBT) program, which delivered mindfulness-based training to parents and children simultaneously in the home environment. This study also implemented a working memory training after PC-MBT to assess the feasibility of completing two trainings sequentially. Healthy children, ages 8-10 ( n = 14), and their parents participated in the PC-MBT program. They met with an instructor at home and online each week for 6 weeks and were provided resources including books, worksheets, audio recordings, and daily practices to reinforce mindfulness skills. A control group ( n = 8) participated in the working memory training only. All PC-MBT and control children, except one, participated in the working memory training. All PC-MBT assigned families completed the PC-MBT program, and a majority utilized all types of the mindfulness training materials. A majority of participants also reported high levels of enjoyment and understanding of the PC-MBT program. This study establishes the feasibility and acceptability of the PC-MBT program and lays the foundation for future studies to assess program efficacy in healthy and clinical populations as well as the utility of PC-MBT to improve engagement and outcomes of other cognitive training programs.